University–Industry Collaboration in Enhancing Professional Competence - GULNAR FARMAN HUSEYNOVA (Theoretical Hypotheses and Empirical Results, 2026)
The increasing complexity of the global labor market, driven by rapid technological advancement and economic integration, has intensified the demand for graduates who possess well-developed professional competencies. However, traditional higher education models often demonstrate limited effectiveness in preparing students for real-world professional environments. This article examines university–industry collaboration as a strategic pedagogical approach aimed at addressing this discrepancy. Drawing upon contemporary educational theories and relevant scholarly literature, the study analyzes the contribution of collaborative practices to the development of professional competence. Particular attention is given to experiential learning opportunities, curriculum alignment, and knowledge exchange mechanisms. The findings indicate that structured collaboration between academic institutions and industry significantly enhances students’ employability, fosters transferable skills, and ensures the relevance of educational programs. The article concludes by emphasizing the necessity of institutional support and strategic planning to sustain effective partnerships.